Tingkat keberhasilan throw in pratama arhan dalam mengancam pertahanan lawan pada laga Timnas Indonesia di ajang Sea Games 2023 - Kusuma, Deny Wijaya; Darumoyo, Kuncoro; Bayu Utomo, Andy Widhiya (Universitas Hamzanwadi, 2024)
The purpose of this study was to examine the success rate of throwing in pratama arhan in threatening the opponent's defense in the Indonesian national team match at the 2023 Sea Games. This research uses a quantitative descriptive method which aims to get a picture of a situation objectively using measurements, data collection is done by observing videos of throws into pratama arhan. The data obtained is processed by the technique of determining the percentage of throws. The results obtained are 33.3% The success rate of throwing into pratama arhan in threatening the opponent's defense. With these results, the pratama arhan throw can be concluded to be quite threatening and can endanger the opponent's defense.